ANALISIS PENGELOLAAN KEUANGAN DESA DENGAN PRINSIP OPEN GOVERNMENT (STUDI KASUS: DESA PEJAMBON KABUPATEN BOJONEGORO) - Wijayanti, Sifa Herdini Sekar (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study was aimed to see the implementation of Open Government principle in financial management of Pejambon Village with the issues faced and the Open Government concept development strategy in village financial management. This study was conducted by using descriptive qualitative method with interview, observation, and documentation as the data collection techniques. The result of this study showed that the financial management of Pejambon Village was had corresponded closely with the accountability, transparency, participation, and orderly budget principle used. However, the problems faced could rise information users’ opinion that the village government did mark-up since performance-based budgeting had not been implemented, there was lack of validation on working plan and budgeting and working realization report and budgeting published, and there were some villagers not knowing Open Government and those who are passive. To improve the village financial management development, Pejambon Village had prepared some strategies such as maintaining village government consistency, constructing village museum in the future, implementing affordable internet, and training for Pejambon villagers.In creating the recommendations, use SWOT analysis. The recommendation is focusing on controlling each procedure, implementing redundancy in the regeneration of infrastructure, labor demand, and updating and improving the analysis results on the knowledge management website, and increasing employee competency. Keywords: open government, village financial management, accountability, transparency, participation, and orderly also discipline budgeting